Heptad green metrics and quality by design tool evaluated chromatography method for content determination of Bexagliflozin in formulation product - Satyajit Raj Nethekar; Phani Raja Kanuparthy; Leela Prasad Kowtharapu; Vishnuvardhana Kishore Polisetti; Pankaj Kumar Lahoti; Sreekantha B Jonnalagadda; Naresh Kumar Katari (Green Analytical Chemistry)
The study created an eco-friendly, rapid, sensitive, cost-efficient, stability-assessing method for analyzing Bexagliflozin in pharmaceuticals using a RP-UPLC approach. The method's specificity was achieved using an XBridge analytical column (100 mm x 2.1 mm, 3.5 µm) with a mobile phase consisting of 10 mM Ammonium acetate and Methanol in a ratio of 55:45 (v/v). The flow rate is 0.2 mL/min, the injection volume is 1 µL, and the UV detection wavelength is 220 nm. The total run time is 2.5 minutes. The technique was meticulously validated, strictly adhering to the ICH criteria, and demonstrated specificity, linearity, ruggedness, robustness, and accuracy. The technique robustness analysis was carried out by using the QbD tool to build DoE's and assess their robustness. The methodology exhibited a linear trend as the concentration level increased from 5µg/mL to 30ug/mL. The recovery process ranged from 50% to 150%, with the average recovery considered adequate. Method stability indicating nature proved by forced degradation study. Analytical Eco-scale value found 81. NEMI showing the three quadrants showing the green, Modified NEMI has only one red quadrant. GAPI have five green, 5 yellow and 5 red parts. Complex GAPI have 12 green, 7 yellow and 6 red parts in the whole pictogram. AGREE shown the quantitative value 0.64 and pictogram shown 7 green parts, three yellow parts and 2 red parts. Green metric tools NEMI, modified NEMI, GAPI, complex GAPI Eco-scale, AGREE, and AGREEprep are used to express the method's greenness.